Stabilization of the Max Homodimer with a Small Molecule Attenuates Myc-Driven Transcription. Issue 5 (16th May 2019) - Struntz, Nicholas B.; Chen, Andrew; Deutzmann, Anja; Wilson, Robert M.; Stefan, Eric; Evans, Helen L.; Ramirez, Maricela A.; Liang, Tong; Caballero, Francisco; Wildschut, Mattheus H.E.; Neel, Dylan V.; Freeman, David B.; et al.
Summary: The transcription factor Max is a basic-helix-loop-helix leucine zipper (bHLHLZ) protein that forms homodimers or interacts with other bHLHLZ proteins, including Myc and Mxd proteins. Among this dynamic network of interactions, the Myc/Max heterodimer has crucial roles in regulating normal cellular processes, but its transcriptional activity is deregulated in a majority of human cancers. Despite this significance, the arsenal of high-quality chemical probes to interrogate these proteins remains limited. We used small molecule microarrays to identify compounds that bind Max in a mechanistically unbiased manner. We discovered the asymmetric polycyclic lactam, KI-MS2-008, which stabilizes the Max homodimer while reducing Myc protein and Myc-regulated transcript levels. KI-MS2-008 also decreases viable cancer cell growth in a Myc-dependent manner and suppresses tumor growth in vivo . This approach demonstrates the feasibility of modulating Max with small molecules and supports altering Max dimerization as an alternative approach to targeting Myc. Graphical Abstract: Highlights: KI-MS2-008 is a Max-binding small molecule that attenuates Myc-driven transcription The compound stabilizes the Max homodimer Effects on DNA occupancy and the transcriptome resemble loss of Myc Treatment withKI-MS2-008 exhibits efficacy in cellular and murine cancer models Abstract : Myc/Max-mediated transcription is deregulated in most of human cancers. Struntz et al. discovered a small molecule that stabilizes the Max homodimer and attenuates Myc-driven transcription with efficacy in cellular and murine cancer models. This discovery reinforces an alternative Myc-targeting strategy and could inform development of compounds to treat Myc-dependent cancers.